EVALUATION OF OPTIMUM LEARNING STYLE TO ENHANCE ENGINEERING EDUCATION - P L N, Ramesh P L N; L, Vanitha; P, Punita; P, Malathi (International Journal of Psychosocial Rehabilitation, 2020)
The learning styles differ among individuals according to their characteristics. An appropriate learning style helps the students to achieve excellent academic performance. In this work, the main objective is to determine the learning stylespreference and also the scale of preference midst engineering students. The students’ preference is also analyzed and compared between different engineering disciplines. Two hundred students distributed between six disciplines Biotechnology, Civil Engineering, Computer Science and Engineering (CSE), Electronics and Communication Engineering (ECE), Electrical and Electronics Engineering (EEE), and MechanicalEngineering disciplines are considered for analysis. Felder Silverman Learning Style Model (FSLSM) is used to determine the learning style based on four dimensions, and each aspect is sub-analyzed based on the scale of performance as balanced, moderate, and strong. The results of the analysis show that students’ preference is high for visual learning style followed byactivist type of learning. The investigation ofthe scale of preference shows that more number of students are balanced, but few students strongly prefer a particular dimension of learning style. Thus identifying the students'specific learning style and educating them according to their choice will help them to enhance individual academic performance and also the overall performance of the institution.